Gynecological Oncology Surgery During COVID-19 Pandemic: What We Should Know - Kayastha, Suresh (Journal of Lumbini Medical College, 2020)
Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2) that causes Corona Virus Disease -19 (COVID-19) is a novel virus and hence humans do not have any prior immunity to it. Every human being is susceptible to this viral infection and rapid spread worldwide made WHO declare it as a global pandemic. Cancer patients are even more vulnerable not only because they are immunocompromised by the disease process itself, but also due to potential effect of chemotherapy, radiotherapy along with substantial effect on their timing of treatment. Patients older than 65 years, and those with pre-existing co-morbidities are considered more at risk. Considering the increased chances of intensive care unit admission, need of mechanical ventilation and possible mortality, all cancer patients should be educated about preventive measures, personal protection, social distancing and isolation. Another possible impact of COVID-19 could be delays in initial evaluation, diagnosis and initiation of actual treatment which are independent risk factors for cancer related mortality. This is due to limited services provided at the health care facilities, lockdown effects, fear of being infected and economic crisis.